Pengaruh Faktor Karakteristik Demografis Dewan Dan Tata Kelola Perusahaan Terhadap Penghindaran Pajak Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Kennardi Tanujaya; Willy Kaslianto (Universitas Internasional Batam, 2021)
The purpose of this study was to determine the effect of female boards of directors, size of directors, executive character, company size, institutional ownership, independent commissioners, audit committee, and audit quality on tax avoidance. The measurement of tax avoidance uses effective tax rates and book-tax differences. The population in this study used companies listed on the IDX from 2015-2019. Based on the purposive sampling method, 153 companies were used as samples. The results showed that the female board of directors, the board size, company size had an influence on BTD, while the character of the executive and the audit committee had an influence on ETR. Well-designed corporate governance within the company can reduce the potential for tax avoidance.